Ethical and Legal Aspects of Punishment and Imprisonment - Igrački, Jasmina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
The paper deals with a prison sentence in contemporary society, its impact on crime prevention, the advantages and disadvantages of the penalty and liberty deprivation effects. The paper also provides an overview of different understandings of imprisonment and punishment through the historical prism, with special emphasis on contemporary ethical-legal interpretations of the sentence and punishment. The author argues that nothing in particular stands out in the punishment in relation to the other measures, but it is only considered the most effective means to reduce crime rates. In order to avoid further suffering, the threat of punishment can deter potential offenders and those convicted of repeated commission. Disabling offenders by imprisonment or strict control of freedom should prevent criminal activities within a certain time period. The important role of prison sentences in the contemporary system of criminal sanctions is based on the expectation that the mere threat of imprisonment has a significant general preventive effect. It is indisputable that a prison sentence is one of the most effective criminal sanctions in the fight against crime. On the other hand, a prison sentence carries many negative consequences for the convicted person, and this is one of the most important reasons for alternative measures, which should remove the negative effects of the prison sentence.